Sodar measurements (Arctic Data Center, 2010)
This data set contains measurements from a SOnic Detection And Ranging (SODAR) that is deployed at Summit Station, Greenland. By transmitting and detecting backscattered sound waves, it provides information on the boundary layer height. Detailed information on this measured parameter and other aspects of the dataset are included in the netCDF header information for each file. The Precipitation Occurrence Sensor System (POSS) is owned by the National Oceanic and Atmospheric Administration's Earth System Research Laboratory. Field operations support is provided by the National Science Foundation's Arctic Observing Network (AON) Program.